Pain in fibromyalgia and related conditions - G. Cassisi; P. Sarzi-Puttini; R. Casale; M. Cazzola; L. Boccassini; F. Atzeni; S. Stisi (PAGEPress Publications, 2014)
Pain is the hallmark symptom of fibromyalgia (FM) and other related syndromes, but quite different from that of other rheumatic diseases, which depends on the degree of damage or inflammation in peripheral tissues. Sufferers are often defined as patients with chronic pain without an underlying mechanistic cause, and these syndromes and their symptoms are most appropriately described as "central pain", "neuropathic pain", "nonnociceptive pain" or "central sensitivity syndromes". The pain is particular, regional or widespread, and mainly relates to the musculoskeletal system; hyperalgesia or allodynia are typical. Its origin is currently considered to be distorted pain or sensory processing, rather than a local or regional abnormality. FM is probably the most important and extensively described central pain syndrome, but the characteristics and features of FM-related pain are similar in other disorders of particular interest for rheumatologists, such as myofascial pain syndromes and temporo-mandibular joint disorders, and there is also an intriguing overlap between FM and benign joint hypermobility syndrome. This suggests that the distinctive aspects of pain in these idiopathic or functional conditions is caused by central nervous system hypersensitivity and abnormalities. Pharmacological and non-pharmacological therapies have been suggested for the treatment of these conditions, but a multidisciplinary approach is required in order to reduce the abnormal cycle of pain amplification and the related maladaptive and self-limiting behaviours.